Unsustainable development pathways caused by tropical deforestation - Carrasco, Luis Roman (Sci Adv, 2017)
Global sustainability strategies require assessing whether countries’ development trajectories are sustainable over time. However, sustainability assessments are limited because losses of natural capital and its ecosystem services through deforestation have not been comprehensively incorporated into national accounts. We update the national accounts of 80 nations that underwent tropical deforestation from 2000 to 2012 and evaluate their development trajectories using weak and strong sustainability criteria. Weak sustainability requires that countries do not decrease their aggregate capital over time. We adopt a strong sustainability criterion that countries do not decrease the value of their forest ecosystem services with respect to the year 2000. We identify several groups of countries: countries, such as Sri Lanka, Bangladesh, and India, that present sustainable development trajectories under both weak and strong sustainability criteria; countries, such as Brazil, Peru, and Indonesia, that present weak sustainable development but fail the strong sustainability criterion as a result of rapid losses of ecosystem services; countries, such as Madagascar, Laos, and Papua New Guinea, that present unsustainable development pathways as a result of deforestation; and countries, such as Democratic Republic of Congo and Sierra Leone, in which deforestation aggravates already unsustainable pathways. Our results reveal a large number of countries where tropical deforestation is both damaging to nature and not compensated by development in other sectors, thus compromising the well-being of their future generations.